Alteration in methylation level at differential methylated regions of MEST and DLK1 in fetus of preeclampsia. (2nd January 2018) - Wang, Xiaoqing; Wan, Liuxia; Weng, Xiaoling; Xie, Jiamin; Zhang, Aiping; Liu, Yun; Dong, Minyue
ABSTRACT: Objectives : Offspring born to preeclamptic women are at high risk for metabolic diseases in later life, but the mechanisms are not known. The purposes of the current investigation were to clarify the changes in DNA methylation at MEST and DLK1 DMRs in fetus of preeclampsia and to explore the possible mechanisms behind the high risk of adult diseases in the offspring of preeclampsia. Methods : Fetal lymphocytes were isolated from umbilical cord blood of 78 women with preeclampsia and 95 women with normal pregnancy. Genomic DNA was extracted and then DNA methylation levels of MEST and DLK1 DMRs were determined by MassARRAY quantitative methylation analysis. Results : The methylation levels were detected in 20 CpG sites of MEST DMR and 16 sites of DLK1 DMR. Methylation changes were significantly different at CPG1, 3, 4, 7.8, 15, 18.19, and 20 of MEST between preeclampsia and normal pregnancy (P = 0.014, 0.001, <0.001, <0.001,  = 0.001,  = 0.005, and = 0.003, respectively). Significant differences were also observed at CPG 3 and 9 of DLK1 (P = 0.002 and 0.027, respectively). However, overall methylation at these DMRs were not affected. Conclusion : We conclude methylation changes at some CpG sites of MEST and DLK DMRs in preeclamptic group. This may be among the mechanisms behind the high risk of adult diseases in the later life of offspring born to preeclamptic pregnancies. Abbreviations: DMR: Differentially Methylated Region; MEST: Mesoderm Specific Transcript